Unconscious motivation. Part II: Implicit attitudes and L2 achievement - Al-Hoorie, Ali H. (Studies in Second Language Learning and Teaching, 2016)
This paper investigates the attitudinal/motivational predictors of second language (L2) academic achievement. Young adult learners of English as a foreign language (N = 311) completed several self-report measures and the Single-Target Implicit Association Test. Examination of the motivational profiles of high and low achievers revealed that attachment to the L1 community and the ought-to L2 self were negatively associated with achievement, while explicit attitudes toward the L2 course and implicit attitudes toward L2 speakers were positively associated with it. The relationship between implicit attitudes and achievement could not be explained either by social desirability or by other cognitive confounds, and remained significant after controlling for explicit self-report measures. Explicit–implicit congruence also revealed a similar pattern, in that congruent learners were more open to the L2 community and obtained higher achievement. The results also showed that neither the ideal L2 self nor intended effort had any association with actual L2 achievement, and that intended effort was particularly prone to social desirability biases. Implications of these findings are discussed.